(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2021)
This special number of LANX is entirely dedicated to Maria Teresa Grassi, whose death last year left an unbridgeable void in the Department of Cultural and Environmental Heritage of the University of Milan, and above all among her countless friends, colleagues, collaborators, students and admirers. The large number of responses received to the invitation to participate in this volume testifies to the affection, friendship and esteem that Maria Teresa enjoyed.